A Sistem Penunjang Keputusan dengan Metode AHP Dalam Strategi Pemasaran Travel Umroh dan Haji Pada PT Jabal Rahmah - Budi, Eko Setia; Dewi, Triyana; Wandani, Putri Yolanda; Anggraeni, Yulianti (TIN: Terapan Informatika Nusantara, 2021)
This study discusses the decision support system in the marketing strategy of Umrah and Hajj travel used at PT. Jabal Rahmah Travel Hajj and Umrah, as a company engaged in tourism and a bureau for Umrah and Hajj travel services. In Umrah and Hajj Travel, it has a decision support system which is a system that is able to provide data management functions based on a certain model regarding decision making about the use of communication media that is easy to use and is of interest to the public to obtain information about Umrah and Hajj travel at PT. Rahmah, so that we can recruit pilgrims who want to carry out the pilgrimage and Umrah pilgrimage clearly and in detail. PT. Jabal Rahmah himself has a marketing strategy through 3 communication media, namely through print media such as brochures, social media such as WhatsApp, Facebook, Instagram and which are in great demand through direct marketing such as conducting seminars or even directly meeting influential religious leaders in the surrounding environment and can communicate directly to society. From the application of the concept of marketing strategy used by PT. Jabal Rahmah decision making is done using the Analytical Hierarchy Process (AHP) method. Where this measurement method is used as a ratio scale to take an efficient and effective decision in an effort to offer products and services. So that prospective pilgrims can make decisions about the process steps they will decide at PT. Jabal Rahmah. This study aims to discuss the marketing strategy carried out by PT. Jabal Rahmah uses the Analytical Hierarchy Process (AHP) method to get priority results which are mostly done in marketing to the public.